2001
DOI: 10.1051/0004-6361:20000575
|View full text |Cite
|
Sign up to set email alerts
|

Entropy and astronomical data analysis: Perspectives from multiresolution analysis

Abstract: Abstract. The Maximum Entropy Method is well-known and widely used in image analysis in astronomy. In its standard form it presents certain drawbacks, such an underestimation of the photometry. Various refinements of MEM have been proposed over the years. We review in this paper the main entropy functionals which have been proposed and discuss each of them. We define, from a conceptual point of view, what a good definition of entropy should be in the framework of astronomical data processing. We show how a def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 37 publications
0
58
0
Order By: Relevance
“…Full details of the minimization algorithm can be found in Starck et al (2001), in addition to a description of how to determine the regularization parameter β automatically.…”
Section: Appendix A: the Fdr Methodsmentioning
confidence: 99%
“…Full details of the minimization algorithm can be found in Starck et al (2001), in addition to a description of how to determine the regularization parameter β automatically.…”
Section: Appendix A: the Fdr Methodsmentioning
confidence: 99%
“…Full details of the minimization algorithm can be found in Starck et al (2001), as well as the way to determine automatically the regularization parameter β.…”
Section: Appendix A: the Fdr Methodsmentioning
confidence: 99%
“…The Maximum Entropy Method (MEM) is well-known and widely used in image analysis in astronomy (see Bridle et al 1998;Starck et al 2001;Marshall et al 2002;, for a full description). It considers both the data and the solution as probability density functions and finds the solution using a Bayesian approach and adding a prior (the entropy) on the solution.…”
Section: Maximum Entropy Methodsmentioning
confidence: 99%
“…More generally MEM method presents many drawbacks (Narayan & Nityananda 1986;Starck et al 2001) and various refinements of MEM have been proposed over the years (Weir 1992;Bontekoe et al 1994;Pantin & Starck 1996;Starck et al 2001). The last developments have led to the so called Multiscale Entropy (Pantin & Starck 1996;Starck et al 2001;Maisinger et al 2004) which is based on an undecimated isotropic wavelet transform (à trous algorithm) (Starck et al 1998). It has been shown that the main MEM drawbacks (model dependent solution, oversmoothing of compact objects, .…”
Section: Maximum Entropy Methodsmentioning
confidence: 99%
See 1 more Smart Citation